2013
DOI: 10.1016/j.radonc.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Normal tissue complication probability (NTCP) parameters for breast fibrosis: Pooled results from two randomised trials

Abstract: a b s t r a c tIntroduction: The dose-volume effect of radiation therapy on breast tissue is poorly understood. We estimate NTCP parameters for breast fibrosis after external beam radiotherapy. Materials and methods: We pooled individual patient data of 5856 patients from 2 trials including whole breast irradiation followed with or without a boost. A two-compartment dose volume histogram model was used with boost volume as the first compartment and the remaining breast volume as second compartment. Results fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 39 publications
2
28
0
1
Order By: Relevance
“…Patient characteristics, such as large breast volume, smoking, and high body mass index (>25 kg/m 2 ), have been associated with increased risk of acute dermatitis . Treatment‐related factors, such as prior chemotherapy treatment, concurrent hormonal therapy, RT fraction size (standard fractionation versus hypofractionated RT), intensity modulated RT (IMRT) vs conventional 3D conformal RT, use of lumpectomy boost, and overall maximum radiotherapy dose within the breast, have also been associated with increased acute cutaneous toxicity …”
Section: Introductionmentioning
confidence: 99%
“…Patient characteristics, such as large breast volume, smoking, and high body mass index (>25 kg/m 2 ), have been associated with increased risk of acute dermatitis . Treatment‐related factors, such as prior chemotherapy treatment, concurrent hormonal therapy, RT fraction size (standard fractionation versus hypofractionated RT), intensity modulated RT (IMRT) vs conventional 3D conformal RT, use of lumpectomy boost, and overall maximum radiotherapy dose within the breast, have also been associated with increased acute cutaneous toxicity …”
Section: Introductionmentioning
confidence: 99%
“…These estimates are likely to be further reduced by the volume effect of late-reacting normal tissues. Thus the tissue tolerance is increased when the volume exposed to critical doses is reduced [129, 130] although recent evidence suggests that the effect may be weak for breast fibrosis [131]. Pneumonitis has not been reported for the TARGIT trial but the ELIOT trial found less lung toxicity in the IOERT compared with the EBRT arm and similar rates of breast fibrosis in the two arms [123].…”
Section: Introductionmentioning
confidence: 99%
“…For IORT boost with LEX, moderate to severe fibrosis at 36 months follow-up was observed in 43 and 31% of the patients treated with an intervals shorter and longer than 5-week, respectively [132]. The latter value may be compared with rates of approximately 20% at 3 years, rising to 28.1% at 10 years and 30.4% at 20 years, in the EORTC boost trial [134136] and with approximately 25% at 5 years for a boost in the 25 × 2 Gy control arm of the START pilot trial [131]. Although the fibrosis rates after an IORT boost appears somewhat increased relative to a standard fractionated EBRT boost of 16 Gy, it compares favourably with the higher rates of 40–55% observed after a boost dose of 26 Gy in the EORTC boost trial [136].…”
Section: Introductionmentioning
confidence: 99%
“…The dose inhomogeneities have been correlated with radiation-induced dermatitis, acute desquamation and late soft-tissue fibrosis and the quality of life of the treated patients has been reported to decline by these physical symptoms. [5][6][7][8] The use of a volumetric modulated arc therapy (VMAT) has steadily increased in external beam radiotherapy. In VMAT the radiation dose is delivered by continuously varying gantry speed, field shape and dose rate.…”
Section: Introductionmentioning
confidence: 99%